Divine Omnipotence, Divine Sovereignty and Moral Constraints on the Prevention of Evil: A Reply to Sterba - Eric Reitan (Religions, 2022)
In Is a Good God Logically Possible?, James Sterba uses the analogy of a just political state to develop evil-prevention principles he thinks a good God would follow. With the assumption that God is omnipotent, these principles entail that God would never permit free agents to bring about horrendous evil. But free agents routinely succeed in doing so: entailing a logical incompatibility between the world’s evils and the existence of a good, omnipotent God. I challenge this conclusion by sketching two ways divine omnipotence arguably entails that God would face moral constraints on the prevention of moral evil that human agents and political states do not. If my account is sound, God would be morally precluded from functioning as a sovereign governing authority in the manner of just political states. If this is correct, Sterba’s arguments might be taken to show, not that there is a contradiction between the world’s evil and the existence of a good, almighty God, but that there is a contradiction between the world’s evil and the common theistic belief that such a God is the sovereign ruler of the world.